Trends of academic achievement of higher education students in Ethiopia: literature review - Kassaw, Chalachew; Demareva, Valeriia; Herut, Adane Hailu (Frontiers in Education, 2024)
This literature review explores trends in academic performance among higher education students in Ethiopia from 2005 to 2022. Its goal is to identify the factors that affect academic success and suggest ways to enhance it. By conducting a thorough search on Google Scholar, relevant studies were selected based on specific criteria, particularly focusing on metrics like GPA. The findings highlight notable differences in student performance, often related to socioeconomic status and the resources available at various institutions. While some universities have seen improvements in GPA, challenges such as overcrowded classrooms and limited support services remain significant obstacles. To address these issues, the review suggests implementing initiatives that promote equity, improving the quality of teaching, and expanding comprehensive support services for students. It stresses the importance of collaboration among all stakeholders to create an inclusive educational environment. Such a holistic strategy is crucial for improving the quality of higher education in Ethiopia and ensuring that all students have equal access to opportunities.